2015
DOI: 10.3310/hta19740
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cost-effectiveness model for optimisation of the screening interval in diabetic retinopathy screening

Abstract: BackgroundThe English NHS Diabetic Eye Screening Programme was established in 2003. Eligible people are invited annually for digital retinal photography screening. Those found to have potentially sight-threatening diabetic retinopathy (STDR) are referred to surveillance clinics or to Hospital Eye Services.ObjectivesTo determine whether personalised screening intervals are cost-effective.DesignRisk factors were identified in Gloucestershire, UK using survival modelling. A probabilistic decision hidden (unobserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(190 citation statements)
references
References 76 publications
8
179
2
1
Order By: Relevance
“…There is limited evidence on the cost-effectiveness of optimal screening intervals for DR. A recent health technology assessment in the UK found DR screening every 3 years, irrespective of risk, was most likely to be cost-effective, while screening every 5 years for low-risk groups and every 2 years for high-risk groups was cost-effective 42. Our review showed similar findings using teleophthalmology as a screening strategy showing frequency up to twice-in-a-lifetime, once every 5, 3 or 2 years increased cost and QALYs gained and remained cost-effective; however, annual screening was not as cost-effective 23…”
Section: Discussionmentioning
confidence: 99%
“…There is limited evidence on the cost-effectiveness of optimal screening intervals for DR. A recent health technology assessment in the UK found DR screening every 3 years, irrespective of risk, was most likely to be cost-effective, while screening every 5 years for low-risk groups and every 2 years for high-risk groups was cost-effective 42. Our review showed similar findings using teleophthalmology as a screening strategy showing frequency up to twice-in-a-lifetime, once every 5, 3 or 2 years increased cost and QALYs gained and remained cost-effective; however, annual screening was not as cost-effective 23…”
Section: Discussionmentioning
confidence: 99%
“…An RCE development dataset was extracted from the data warehouse containing covariates with ≥ 80% completeness in people with diabetes who were screen negative (non-referable retinopathy) at the first of at least two episodes that occurred in a 5 year sample period. Disease duration was defined as duration of known diabetes mellitus (first recorded date of diabetes or measure of HbA 1c in primary care [11]) and assigned at the first screening episode. Values of clinical risk factors prior and nearest to the screen episode date were used.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, adopting biennial screening approach, a reduction in approximately 25% of screening costs can be obtained without increased risk to the patient [44]. Two recent studies reported cost-effectiveness of adopting risk-stratified approaches to extended screening intervals in the national DR screening programs in England and Scotland [45, 46]. Scanlon et al conducted a modelling study and reported that for patients without DR on two consecutive screening examinations the adoption of 2-year screening intervals would save on average 225000 pounds per QUALY (quality-adjusted life years) lost compared with annual screening in England [45].…”
Section: Telemedicine Screening Programs In Italymentioning
confidence: 99%